(untitled) (Research, Society and Development, 2020)
This article aims to discuss the importance of continuing teacher education through the narrative of the work routine of professionals working in the Youth and Adult Education Program - PEJA - of Rio de Janeiro City Hall. For data collection, direct observation and follow-up of weekly meetings were used for continuing education purposes, along with the application of a questionnaire to the teachers involved. This report highlights the importance of weekly meetings that are common to the routine of these teachers, as a way of enriching the planning, obtaining new learning and reinforcing the ’conversations’ between the subjects, corroborating the integration of different knowledge. The experience narrated reinforces the conception that these weekly meetings allow the dialogue between the subjects and the collective construction of contextualized classes, which is one of the differentials obtained through the continuing education of these teachers.